2015
DOI: 10.1108/joepp-08-2014-0042
|View full text |Cite
|
Sign up to set email alerts
|

Employee engagement, human resource management practices and competitive advantage

Abstract: Purpose – The purpose of this paper is to argue in support of a model that shows how four key HRM practices focused on engagement influence organizational climate, job demands and job resources, the psychological experiences of safety, meaningfulness and availability at work, employee engagement, and individual, group and organizational performance and competitive advantage. Design/methodology/approach – This conceptual review focuses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
461
1
36

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 567 publications
(601 citation statements)
references
References 126 publications
22
461
1
36
Order By: Relevance
“…Studies focusing on work engagement and inherently pride showed that commitment with the organization, job satisfaction, and public service motivation are job attitudes which work in tandem to produce organizational outcomes (Albrecht et al, 2015;Perry & Vandenabeele, 2015). Lavigna (2015) argues that public organizations should recruit and retain employees who have a high degree of PSM and then build on that gene to drive high levels of engagement and inherently pride.…”
Section: Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…Studies focusing on work engagement and inherently pride showed that commitment with the organization, job satisfaction, and public service motivation are job attitudes which work in tandem to produce organizational outcomes (Albrecht et al, 2015;Perry & Vandenabeele, 2015). Lavigna (2015) argues that public organizations should recruit and retain employees who have a high degree of PSM and then build on that gene to drive high levels of engagement and inherently pride.…”
Section: Theorymentioning
confidence: 99%
“…As mentioned in the introduction, while the JD-R model is focused on the work environment and work experience of employees, the HPWPS taxonomy is focused on concrete instruments. Albrecht et al (2015) theorized that a combination might have a positive effect on work engagement and inherently pride. Bakker and Demerouti (2014) argue that the effects of these determinants might depend on the specific occupation under consideration.…”
Section: The Determinants Of Professional Pridementioning
confidence: 99%
See 3 more Smart Citations